“Don’t leave us behind”: a qualitative study exploring the feasibility of a palliative care training program for non-health caregivers in Honduras - Sheryl Ruiz; Martin Stafström; Leda Parham; Luis Orellana (Palliative Care and Social Practice)
Background: Palliative care (PC) can alleviate suffering and improve quality of life. Yet, disparities persist, particularly in Honduras. Training efforts in PC for non-health caregivers have proven to reduce burnout and stress while enhancing the quality of life for both caregivers and patients. Purpose: This study aimed to explore the feasibility of a PC training program for non-health caregivers in Honduras. Methods: This exploratory study utilized latent content analysis within an interpretivist paradigm. Data was collected through individual semi-structured interviews with 25 participants belonging to different key groups: patients diagnosed with cancer, non-health caregivers, PC experts, and health-related decision makers. Interviews were conducted in Honduras’ three main cities: Tegucigalpa, San Pedro Sula, and La Ceiba. The sampling technique employed was maximum variation. Results: PC patients and caregivers face significant emotional challenges, often worsened by poverty and resource limitations, which leads to a strain in family dynamics. A lack of education, driven by inadequate healthcare education and policies, contributes to widespread misconceptions about PC. However, progress through various sectors aligned with the same goals proves Honduras is a country with potential. A program with a bottom-up approach, with intersectoral collaboration and training tailored to the needs of caregivers and patients, is urgently needed. Conclusion: It highlights the feasibility, necessity, and potential replicability of implementing a PC training program for non-health caregivers in Honduras, which could offer significant benefits at both individual and national levels. A program that truly accounts for health determinants may help mitigate PC shortages in similar regions. Further research and policy advocacy are essential to empower underserved populations and foster health equity across low- and middle-income settings, to ensure no one is left behind.